An investigation of the current situation of the Mısırlıoğlu Bridge and possible damages after freeze-thaw by using finite elements analysis, Sille – Konya (Central Anatolia, Turkey). (November 2020) - Saydan, Murat; Unal, Alptug; Keskin, Ulku Sultan; Kansun, Gursel
Highlights: The mechanical properties of volcanic stones used in a masonry bridge are determined. The numerical analysis of the bridge before and after freeze-thaw test were evaluated. The causes of damage in the bridge were examined. Abstract: This study examines Mısırlıoğlu Bridge built with Sille stone located in the Sille district of Konya, one of the oldest settlements in Turkey. Three different Sille stone types that were used in various parts of the bridge were defined petrographically, despite their similar look from the outside. Samples were obtained from regional stone quarries with similar characteristics with these defined stones. Geochemical, physical, and mechanical tests were conducted on these samples. In addition to these tests, a group of samples were subjected to freeze-thaw cycles, and their mechanical features were defined after freeze-thaw. A numerical model of the bridge was built using the characteristic of the obtained material, and the structural situation before and after the freeze-thaw was analyzed on this model under the current loads. The results indicated that stress distributed normally over the bridge under current loads before freeze-thaw, displaced more compared to the other model while the displacement level remained limited after conducting freeze-thaw, losing its bearing capacity very soon. On the other hand, the stresses distribution on the bridge was spread over the entire surface before freeze-thaw while they were concentrated in a local area after freeze-thaw. Furthermore, the maximum compressive strain values of stones used in the bridge were determined and it was observed that the values were larger than the result obtained from before the freeze-thaw model. In particular, the landscape work carried out in recent years caused water to be retained underneath the bridge. Due to this, freeze-thaw is expected to intensify around the bridge piers, which leads us to assess the necessity to build the bridge using Sille stones with high mechanical durability.